Opportunities and challenges of international Chinese language education in general secondary education institutions (case of Belarus) - Hryshayeva, Katsiaryna S.; Dai, Manchun; Oubibi, Mohamed (University Pedagogical Journal, 2026)
This article examines the development of international Chinese language education in Belarus in the context of the deepening Belarusian-Chinese strategic partnership. Key characteristics of international Chinese language education in Belarus are analysed, and prospects and challenges affecting its sustainability and development are identified.